The Influence of Harvesting Period on Lipid Associated Antioxidant Activity of Semicontinuously Grown Chlorella vulgaris - Chrismadha, Tjandara; Sartika, Diani; Setyaningsih, Iriani; Uju, Uju (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2010)
A green alga,Â Chlorella vulgarisÂ was grown semi-continuosly at various harvesting periods, and the lipid content and its associated antioxidant activity was examined. The harvesting periods were 9, 18, and 27 days, while the algal culture was placedÂ in 10 L glassÂ bottles provided with aerationÂ for gas exchange andÂ mixing. LightÂ wasÂ obtainedÂ fromÂ 4ï´40Â wattÂ coolÂ fluorescentÂ lampsÂ placedÂ atÂ oneÂ sideÂ ofÂ theÂ culture.Â Room temperature wasÂ 26-32ï°C.Â AlgalÂ lipidÂ extractionÂ wasÂ doneÂ basedÂ onÂ liquidÂ phaseÂ separationÂ of Â methanol :chloroform:waterÂ andÂ theÂ antioxidantÂ activityÂ wasÂ examinedÂ byÂ meansÂ ofÂ oxidationÂ inhibitoryÂ in ethanol emulsifiedÂ limnoleicÂ acid.Â InÂ addition,Â aÂ TLCÂ analysisÂ wasÂ performedÂ toÂ identifyÂ theÂ antioxidant compouns solubleÂ inÂ theÂ lipid.Â TheÂ resultsÂ showedÂ thatÂ harvestingÂ per iodÂ hadÂ aÂ significantÂ influenceÂ onÂ the algal lipidÂ content,Â whichÂ wereÂ 11.94,Â 12.96,Â andÂ 16.51%Â ofÂ theÂ dryÂ weightÂ inÂ theÂ cultureÂ withÂ harvesting periods of 9, 18, and 27 days, respectively. No remarkable effect of theÂ harvesting period on theÂ antioxidant activity, which were observed to inhibit oxidation of linoleic acid up to 67-71%. There were five compounds found canÂ be associated Â Â withÂ theÂ algalÂ antioxidantÂ activity,Â whichÂ wereÂ pheophorbide -a,Â chlorophyll-b,chlorophyll-a, phaeophytin-a, ï¢-carotene, and an unidentified one.Â Key words: microalgae, Chlorella vulgaris, lipid, antioxidant, harvesting periodÂ